PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR SISWA KELAS X TEKNIK AUDIO VIDEO PADA MATA DIKLAT KETERAMPILAN DASAR ELEKTRONIKA DI SMK NEGERI 1 LINTAU BUO - Veni Effendi; Hanesman Hanesman; Sukaya Sukaya (Universitas Negeri Padang, 2014)
The problem in this research is the discovered fact that in SMK Negeri 1 Lintau, the number of grade X.TAV students obtain a learning outcomes under the KKM on subject Keterampilan Dasar Elektronika that set by school is 80. 65,39% of students under the KKM and 34,61% of students over the KKM. One of the affect factors is the learning model. This study aimed to see differences in learning outcomes with STAD cooperative learning type and direct instruction. This study uses experimental approach, the population is X.TAV grade students of SMK Negeri 1 Lintau Buo. The Sampling technique is saturated samples. The experiments Class using STAD Cooperative Learning type and the control class using direct instruction. Collected data from results of a study with objective test. Data were analyzed manually to test for normality, homogeneity testing, and hypothesis testing. Results were obtained an average value of students who use STAD Cooperative Learning is 78.13 while students who use direct instructional methods is 68.26. The results of hypothesis using the manually formula get tcount 2,311> 1,701 t table, so that the alternative hypothesis (Ha) is accepted or rejected the null hypothesis (Ho). Keyword : Model Pembelajaran, Pembelajaran Kooperatif tipe STAD, Pembelajaran Langsung.